Uji Efektivitas Ekstrak Daun Cengkeh (Syzigium Aromaticum) Sebagai Repellent Semprot Terhadap Lalat Rumah (Musca Domestica) - Nur Aliah; Andi Susilawaty; Irviani Anwar Ibrahim (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2016)
Housefly (Musca domestica) can act as vectors of disease typus, other stomach diseases such as dysentery and diarrhea, cholera and skin diseases. The use of insect repellent is generally not lethal but rather serves to reject the presence of insects. The content of the clove leaf that serves as a repellent against the house fly are: essential oil or eugenol which typically pungent aroma and flavonoid pungent and bitter tastes that are not favored by the house fly (Musca domestica). The purpose of this study was to determine how the effectiveness of extracts of clove (Syzygium aromaticum) as a repellent (repellent) houseflies (Musca domestica) with a spray method, and the concentration of how much of the leaf extract of clove (Syzygium aromaticum) is effective as a repellent (repellent) flies home (Musca domestica) with a spray method. This research is a quantitative research methods Experiments with real (True Experiment). This research was conducted at the Laboratory of Environmental Health UIN Alauddin Makassar, the sample in this study is the house fly as much as 180 tails were divided into four cages each containing 15 flies to the treatment (0%, 10%, 15% and 20%) and 3 times replication with observation time of 60 minutes. The research results are to be obtained amount of 10% concentration of flies hinggapan I repeat that 10 heads, 10 tails which replicates II, and III that replicates nine tails. At a concentration of 15% which is 4 tails I repeat, repetition II are two tails, and replications III is 2 tails. At a concentration of 20% at I repeat that one tail, replicates II 0 and replicates III, 1 tail. Based on the test results Freidman Asymp.Sig value <0.05 is 0.029 which Ha is received and stated that the leaf extract of clove (Syzygium aroticum L.) is effective as a repellent against the house fly (Musca domestica). The average thrust extract at a concentration of 10%, ie 35.55%, the concentration of 15% ie 82.22% and a concentration of 20% ie 95.55%. The best treatment in preventing hinggapan fly is at a concentration of 20% to 95.55% thrust. The results of this study are expected to be an alternative vector control especially house flies (Musca domestica) as a plant-based repellent spray is environmentally friendly.Keywords : house flies, clove leaf extract, repellent